Quantitative CT Assessment of Emphysema and Its Relationship with Disease Severity - Sajida Majeed, Muhammad Waqas Afzal, Muhammad Rashid Rasool, Muhammad Imran Shahzad, Kashif Sardar, Wajeeha Anwar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emphysema is a key structural component of chronic obstructive pulmonary disease (COPD) and a significant driver of the disease burden and disease progression. While conventional spirometry can give only a limited amount of information about regional lung destruction, whereas quantitative computed tomography (CT) offers objective assessment of emphysema severity. Objective: To evaluate quantitative CT measures of emphysema and determine their relationship with clinical, functional, and radiological indicators of disease severity in patients with COPD. Methods: This was a cross-sectional study of 100 patients with COPD (GOLD diagnosis). PFT and HRCCT of the chest were performed in all participants. Quantitative measurement of emphysema was made by density mask analysis and the areas with low attenuation were below −950 HU, which were then used to calculate the emphysema index, the mean lung density and the total lung volume. Severity of the disease was determined by FEV₁ percentage predicted, GOLD stage, dyspnea score on the modified MRC, oxygen saturation and exacerbation frequency. The statistical analysis were correlation and group comparison tests. Results: The emphysema index mean value was 18.9 ± 10.7%. There was a significant negative correlation between quantitative CT and FEV₁ (% predicted) (r = −0.72, p < 0.001) and FEV₁/FVC ratio. Increased dyspnea scores, decreased oxygen saturation and increased exacerbation burden were significantly associated with higher emphysema burden. Patients with severe emphysema had significant impairment of pulmonary function and clinical outcomes compared with patients with mild disease (p < 0.001). Conclusion: Quantitative CT evaluation of emphysema is a good and reliable index of COPD severity. It has shown a strong correlation with functional impairment and clinical outcomes and should be used in conjunction with spirometry in the comprehensive evaluation, phenotyping and management planning of the disease. Keywords: COPD, emphysema, quantitative computed tomography (CT), lung function, GOLD stage and imaging biomarkers.